Chylothorax as Initial Presentation of Follicular Lymphoma: A Case Report and Literature Search - Gi Eun Kim; Yousif Khaled; Saleh Mahmoud; Amin Ur Rehman (Case Reports in Hematology)
Chylothorax is accumulation of chyle in pleural space. Causes include traumatic, such as after esophagectomy, and nontraumatic, most commonly malignancy. Lymphoma usually presents as asymptomatic lymphadenopathy, and chylothorax tends to occur late in disease course. Chylothorax as initial presentation of lymphoma is rare with only case reports. We present a case of 43-year-old female who presented with dyspnea only with no B symptoms and found to have left-sided chylothorax, and was later diagnosed to have stage IV follicular lymphoma. This case highlights an atypical presentation of follicular lymphoma, to help physicians to reach diagnosis earlier in similar cases.